Blood Groups and their Association with Academic Performance among Medical Students in a Nepalese Medical College - Mahat, Barun; Shrestha, Lava; Adhikari, Shailesh; Thapa, Bikalp; Limbu, Prakesh; Banstola, Dinesh; Dhungel, Sunil (Journal of Institute of Medicine Nepal, 2019)
Introduction Knowing a person’s blood type is not only important in transfusion medicine and forensic medicine but is also useful for predicting a person’s characteristics including intelligence, knowledge, skill and behavior. It is recognized that intelligence, knowledge and skill are assessed by performance in examination. The objective of this study was to determine distribution of blood groups among students and its association with their academic performance. Methods This was an analytical study that was conducted among the medical students of Nepalese Army Institutes of Health Sciences (NAIHS) in Department of Clinical Physiology from June 2014 to April 2019. This study was conducted among 738 students by using convenient sampling method. Blood group was determined on the basis of agglutination reaction. Academic performance of students was assessed by the marks obtained by them in annual final examination. Results Blood group O was the most prevalent at 33.5%, followed by B at 29.5%, A at 29% and AB at 8%. Distribution of Rh positive and Rh negative were 96.6% and 3.4% respectively. The mean scores obtained in final university examination were highest in blood group A (62.9%) and lowest in blood group AB (60.3%) but the difference between different blood groups was not statistically significant. Conclusion Blood group O was the most common blood group. Rh positive was present in 96.6%. Though mean score was highest in blood group A, significant association between blood groups and academic performance was not seen in our study.